МЕЖДУНАРОДНАЯ ЯДЕРНАЯ БЕЗОПАСНОСТЬ КАК СОСТАВЛЯЮЩАЯ МЕЖДУНАРОДНОЙ ЭКОЛОГИЧЕСКОЙ БЕЗОПАСНОСТИ (Journal of actual problems of jurisprudence, 2019)
In the presented article the author discovers the international nuclear safety as a component of the international ecological safety.